Turning confusion into clarity: a guide to the foundation practices of Tibetan Buddhism (Snow Lion, 2014)
Advice and encouragement from a leading spiritual teacher and popular author on how to approach the foundational practices of Tibetan Buddhism For anyone interested in Buddhist practice and philosophy, Turning Confusion into Clarity gives detailed instruction and friendly, inspiring advice for those eager to embark on the Tibetan Buddhist path. By offering guidance on how to approach the process and instruction on specific meditation and contemplation techniques, author and teacher Yongey Mingyur Rinpoche provides gentle yet thorough commentary, companionship, and inspiration for committing to the Vajrayana path.